Genotypic response towards haploid induction in short day tropical Indian onion (Allium cepa) - KHAR, ANIL; KUMAR, ARUN; ISLAM, SABINA; KUMAR, AMRENDER; AGARWAL, ARUN (The Indian Journal of Agricultural Sciences, 2018)
Doubled haploid technology is advantageous for a cross pollinated crop with high inbreeding depression like onion that takes 12 years to develop inbreds through conventional breeding. Inbred development through haploid technology takes only 1 to 2 years and will be a boon for heterosis breeding programme. Two media (HAP02, HAP04) and seven genotypes were assessed for their response towards haploid induction. HAP04 was significantlysuperior to HAP02 for embryo induction. Significant differences in media towards callus formation and significant differences in media and genotypes towards embryo induction were observed. Open pollinated varieties and hybrids were more responsive towards embryo induction followed by exotic and landrace, whereas callus induction was more in landrace. Days for embryo induction were lower in PWF (65-83), whereas RCL was the best respondinggenotype (2.22 shoots/plant) for multiple shoot induction. About 33% plants survived and haploids, spontaneous diploids and tetraploids were obtained. Gamborg's B5 medium supplemented with 2,4-D and BA @ 2 mg/l each was the best media. This study will form a basis for inbred development to accelerate hybrid breeding programme in short day tropical Indian onion.